Securable networked scheme with face authentication - Da‐You Huang; Chun‐Liang Lin; Yang‐Yi Chen (IET Biometrics)
Abstract Recently, facial recognition has been extensively adopted in various fields. Wide applications are associated with a large amount of data transmission so that edge computing is inspired accordingly. In this research task, the major goal of edge computing is to handover a part of the computing work to the terminal equipment; the server only needs to process the results of final return. The IoT configuration proposed includes a perception layer, a transmission layer, and an application layer to fulfil a complete IoT system. In the perception layer, the facial authentication mechanism is adopted. This system is equipped with a highly robust anti‐spoofing function, which can avoid criminal access from photos or electronic screens. Finally, the IoT transmission system is realised as the transmission layer. Combined with such a transmission mechanism, one can distribute user facial features to user's electronic devices instead of storing it in the server. This not only saves storage resources and transmission costs, but also allows users to complete data transmission and face authentication easily.